The potential value of traditional Chinese medicine monomers in cerebral ischemia–reperfusion injury: a network meta-analysis based on animal model - Xin Luo; Jing-Yuan Niu; Hui-Sheng Chen (BMC Complementary Medicine and Therapies)
Abstract Background Cerebral ischemia–reperfusion injury (CIRI) is a complex pathological process, which can further aggravate the damage of ischemic tissues. Traditional Chinese medicine (TCM) monomers, bioactive compounds extracted from Chinese herbal medicines, have been demonstrated to have various protective effects against reperfusion injury. This network meta-analysis (NMA) aimed to investigate the optimal treatment strategy of TCM monomers for CIRI in animal models. Methods Four databases including PubMed, Embase, Web of Science, and Cochrane were searched up to January 06, 2024. First, prospective registration was done at PROSPERO (ID: CRD42024496289), the quality of the included studies was evaluated with SYRCLE's risk of bias tool, and statistical analysis was conducted with Stata Version 18.0 and RStudio. Results In total, 26 studies were included, involving 506 animals and 12 TCM monomers. The results of a meta-analysis demonstrated that, compared to the control group, puerarin, paeoniflorin, hydroxysafflor yellow A, sinomenine, and salvianolic acid significantly reduced mNSS scores. Furthermore, ginsenoside, scutellarin, and baicalein significantly reduced Longa scores. In addition, salvianolic acid treatment significantly decreased brain water content. Regarding infarct volume, bilobalide, baicalein and puerarin all demonstrated remarkable effects. The network meta-analysis suggested that paeoniflorin might be the most effective intervention in terms of mNSS score, with a surface under the cumulative ranking curve (SUCRA) value of 92.8%; Scutellarin might be the most effective intervention to reduce Longa score (SUCRA = 87.6%); And salvianolic acid might be the most effective intervention to reduce brain water content (SUCRA = 98.2%); For infarct volume specifically, bilobalide may be the most effective intervention (SUCRA = 95.5%). In our meta-regression, we found that dose and duration of treatment may contribute to heterogeneity among mNSS studies. Conclusion TCM monomers could provide a favorable neuroprotection on CIRI, with heterogeneous protective effects. Given the small number and the differences in quality of included studies, more high-quality, programmatic animal studies were needed to validate our findings. Clinical trial number Not applicable.